2020
DOI: 10.3390/ijms21176020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biomarkers in Multiple Sclerosis and Its Related Disorders: A Critical Review

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disease affecting the central nervous system (CNS) which can lead to severe disability. Several diseases can mimic the clinical manifestations of MS. This can often lead to a prolonged period that involves numerous tests and investigations before a definitive diagnosis is reached. As well as the possibility of misdiagnosis. Molecular biomarkers can play a unique role in this regard. Molecular biomarkers offer a unique view into the CNS disorders. They help us und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 159 publications
(204 reference statements)
0
9
0
Order By: Relevance
“…The diagnosis is based on the criteria of Macdonald 2017 [4], which above all clinical, reinforced by radiological examinations including cerebral-medular MRI with the study of cerebrospinal fluid. Recently, it has been suggested that the levels of complement specific proteins such as C1q, C3d, and C5b-9 in serum and CSF could potentially serve as new biomarkers to diagnose different MS subtypes and determine the activity of disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is based on the criteria of Macdonald 2017 [4], which above all clinical, reinforced by radiological examinations including cerebral-medular MRI with the study of cerebrospinal fluid. Recently, it has been suggested that the levels of complement specific proteins such as C1q, C3d, and C5b-9 in serum and CSF could potentially serve as new biomarkers to diagnose different MS subtypes and determine the activity of disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers can have several applications, such as the diagnosis of diseases in very early stages, monitoring disease activity, assessing treatment response, and being potential drug targets for novel treatment strategies (77). As regards diagnosis specifically, molecular biomarkers may also help clinicians differentiate MS from other CNS-associated disorders, thus avoiding misdiagnoses (78). Some researchers have already established biomarkers for MS, including CSF biomarkers such as neurofilaments, chitinases, soluble cell surface receptors from microglia and macrophages, and oligoclonal immunoglobulin M antibodies (79).…”
Section: Multiple Sclerosis and Computational Biologymentioning
confidence: 99%
“…MS, a chronic autoimmune inflammatory illness, can affect the CNS and result in severe disability ( Gul et al, 2020 ). The typical clinical symptoms of MS are characterized by weakness, sensory loss, diplopia, decreased vision, etc ( Cunniffe and Coles, 2021 ).…”
Section: The Function Role Of Il-38 In Autoimmune Diseasesmentioning
confidence: 99%